Pengaruh dukungan sosial terhadap motivasi berprestasi akademik dan olahraga pada atlet - Prasetiyo, Rahayu; Yunarta, Arsika (Jurnal Porkes, 2023)
The aim of this study was to find out the effect of social support from parents, coaches, and peers on academic motivation and sports achievement in athletes. This type of research is correlational. The research sample was 45 students who became athletes in the district. Jombang. The sampling technique used purposive sampling. The instrument or measurement tool used to measure academic achievement motivation is the AMI (Achievement Motivation Inventory) questionnaire, achievement motivation uses the Achievement Motivation Scale (AMS) questionnaire and social support questionnaire developed by researchers. The data analysis technique used was multiple correlation which was analyzed using SPSS 23. The results obtained were Sig <0.05, so it can be said that social support, parents, coaches, and peers have an influence on academic and sports achievement motivation. Parental support shows the most significant influence on academic and sports achievement motivation compared to coaches and peers.